Noise Source Identification of Small Fan-BLDC Motor System for Refrigerators - Yong-Han Kim; Bo-Suk Yang; Chang-Joon Kim (International Journal of Rotating Machinery)
Noise levels in household appliances are increasingly attracting attention from manufacturers and customers. Legislation is becoming more severe on acceptable noise levels and low noise is a major marketing point for many products. The latest trend in the refrigerator manufacturing industry is to use brushless DC (BLDC) motors instead of induction motors in order to reduce energy consumption and noise radiation. However, cogging torque from BLDC motor is an undesirable effect that prevents the smooth rotation of the rotor and results in noise. This paper presents a practical approach for identifying the source of excessive noise in the small fan-motor system for household refrigerators. The source is presumed to a mechanical resonance excited by torque ripple of the BLDC motor. By using finite element analysis, natural frequencies and mode shapes of the rotating part of the system are obtained and they are compared with experimental mode shapes obtained by electronic torsional excitation test which uses BLDC motor itself as an exciter. Two experimental validations are carried out to confirm the reduction of excessive noise.